Heat transfer performance of a seawater-source heat pump with radiant floor heating system in cold areas of China. (3rd April 2017) - Zheng, Wandong; Zhang, Huan; You, Shijun; Ye, Tianzhen
Abstract : The thermal performance of seawater-source heat pump with radiant floor heating system during the whole heating season in cold regions of China is studied. High-density polyethylene helical coil heat exchanger and a new type radiant floor heating system with aluminium layer is adopted to improve the thermal performance of the system. The heat transfer characteristics of the heat exchanger in flowing seawater and the thermal resistance of each component is experimentally studied, which will be much helpful in the optimizing of heat exchangers used for the seawater-source heat pump system. The temperature distribution of the radiant floor heating system with aluminium layer is tested and the system thermal efficiency is studied during the whole heating days. The results indicate that the heating system has a large popularizing and utilizing value.